Self-calibrating automated characterization system for depressed cladding EDFA applications Using LabVIEW software with gPIB - Zulkifli, Mohd Zamani; Harun, Sulaiman Wadi; Thambiratnam, Kavintheran; Ahmad, Harith (IEEE, 2008)
A self-calibrating automated characterization system for depressed cladding applications is demonstrated utilizing the Laboratory Virtual Instrument Engineering Workbench (LabVIEW) software and General Purpose Interface Bus (GPIB) interface. The automation system consists of a tunable laser source (TLS), optical spectrum analyzer (OSA), attenuator, laser diode controller, and a personal computer, and all these instruments are networked using GPIB cables. Compared to manual measurement techniques, the overall experiment time is reduced by 80% while the data acquisition increases in accuracy, with a lower uncertainty value of ±0.012 dB after self-calibration. From the experiment, the use of the automated self-calibrating software has allowed for the characterization of the depressed cladding erbium-doped fiber (EDF).